Modulation of Biotransformation Systems and ABC Transporters by Benznidazole in Rats - Perdomo, Virginia (2013)
The effect of antichagasic benznidazole (BZL; 100mg/kg body weight/day, 3 consecutive days, intraperitoneally) on biotransfor-mation systems and ABC transporters was evaluated in rats. Expression of cytochrome P-450 (CYP3A), UDP-glucuronosyltrans-ferase (UGT1A), glutathioneS-transferases (alpha glutathioneS-transferase [GST-], GST-, andGST-), multidrug-resis-tance-associated protein 2 (Mrp2), and P glycoprotein (P-gp) in liver, small intestine, and kidney was estimated by Western blotting. Increases in hepatic CYP3A (30%) andGST-(40%) and in intestinal GST-(72% in jejunumand 136% in ileum) were detected. Significant increases in Mrp2 (300%) and P-gp (500%) proteins in liver from BZL-treated rats were observedwithout changes in kidney. P-gp and Mrp2 were also increased by BZL in jejunum (170%and 120%, respectively). In ileum, only P-gp was increased by BZL (50%). The activities of GST, P-gp, and Mrp2 correlatedwell with the upregulation of proteins in liver and jejunum. Plasma decay of a test dose of BZL (5mg/kg body weight) administered intraduodenally was faster (295%) and the area under the concentration-time curve (AUC) was lower (41%) for BZL-pretreated rats than for controls. The biliary excretion of BZLwas higher (60%) in the BZL group, and urinary excretion of BZL did not showdifferences between groups. The amount of absorbed BZL in intestinal sacs was lower (25%) in pretreated rats than in controls. In conclusion, induction of biotransforma-tion enzymes and/or transporters by BZL could increase the clearance and/or decrease the intestinal absorption of coadminis-tered drugs that are substrates of these systems, including BZL itself.